2015
DOI: 10.1371/journal.pone.0133928
|View full text |Cite
|
Sign up to set email alerts
|

Differential Levels of Alpha-2-Macroglobulin, Haptoglobin and Sero-Transferrin as Adjunct Markers for TB Diagnosis and Disease Progression in the Malnourished Tribal Population of Melghat, India

Abstract: Lack of diagnostic capacity has been a crucial barrier preventing an effective response to the challenges of malnutrition and tuberculosis (TB). Point-of-care diagnostic tests for TB in immuno-incompetent, malnourished population are thus needed to ensure rapid and accurate detection. The aim of the study was to identify potential biomarkers specific for TB infection and progression to overt disease in the malnourished population of Melghat. A prospective cohort study was conducted in the year 2009 through 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…Bapat et al . 7 observed a significant increase in α2M and haptoglobin expression in cases of Mycobacterium tuberculosis infection in humans. Enrichment of α2M with microparticles satisfactorily modulated the immune response and survival in human sepsis 33 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Bapat et al . 7 observed a significant increase in α2M and haptoglobin expression in cases of Mycobacterium tuberculosis infection in humans. Enrichment of α2M with microparticles satisfactorily modulated the immune response and survival in human sepsis 33 .…”
Section: Discussionmentioning
confidence: 79%
“…To elucidate and understand the dynamics of the pathophysiological events during inflammatory reactions, variations of APPs serum levels have been studied in many diseases, such as type 2 diabetes 3 , Alzheimer’s disease 4 , the risk of Parkinson’s disease 5 , the evolution of cancers 6 and in cases of bacterial infections 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that haptoglobin expression increased by nearly twice in patients with latent status to active TB in the malnourished population. [ 46 ] LCN2 plays an antibacterial role by combining with iron carriers required for bacterial growth. Other studies have shown that mycobactin-mediated iron uptake is a prerequisite for intracellular mycobacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma A2M levels in tuberculous lymphadenitis, pulmonary tuberculosis, and latent tuberculosis patients compared to healthy controls suggested a positive correlation between higher A2M levels and progression of mycobacterial infection ( 41 ). Similarly, A2M was also significantly increased in the serum of malnourished patients with active tuberculosis, suggesting a role for A2M in mycobacterial pathogenesis ( 42 ). A2M is mainly synthesized in liver and its production is affected by various cytokines such as TNF-α, IL-1 and IL-6 ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, A2M was also significantly increased in the serum of malnourished patients with active tuberculosis, suggesting a role for A2M in mycobacterial pathogenesis ( 42 ). A2M is mainly synthesized in liver and its production is affected by various cytokines such as TNF-α, IL-1 and IL-6 ( 42 ). In that regard, up-regulation of A2M can be induced by highly abundant pro-inflammatory cytokines in MAP-infected animal.…”
Section: Discussionmentioning
confidence: 99%